2010
DOI: 10.1002/jor.21173
|View full text |Cite
|
Sign up to set email alerts
|

A novel MSC‐seeded triphasic construct for the repair of osteochondral defects

Abstract: Mesenchymal stem cells (MSC) are increasingly replacing chondrocytes in tissue engineering based research for treatment of osteochondral defects. The aim of this work was to determine whether repair of critical-size chronic osteochondral defects in an ovine model using MSC-seeded triphasic constructs would show results comparable to osteochondral autografting (OATS). Triphasic implants were engineered using a beta-tricalcium phosphate osseous phase, an intermediate activated plasma phase, and a collagen I hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 44 publications
1
69
1
Order By: Relevance
“…[35,[42][43][44]. Moreover, Marquass believed that this process most probably occurs in the early post-implantation phase [35]. In our studies, no sinking was found after 3 months of implantation.…”
Section: Resultscontrasting
confidence: 68%
See 3 more Smart Citations
“…[35,[42][43][44]. Moreover, Marquass believed that this process most probably occurs in the early post-implantation phase [35]. In our studies, no sinking was found after 3 months of implantation.…”
Section: Resultscontrasting
confidence: 68%
“…Some studies reported that implant sinking phenomenon was observed after repairing osteochondral defect with implants. [35,[42][43][44]. Moreover, Marquass believed that this process most probably occurs in the early post-implantation phase [35].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Natural materials, including collagen [16,17] fibrin [18], hyaluronan [19], alginate [20] and agarose [21][22][23], have been widely investigated for use in osteochondral tissue repair.…”
Section: Introductionmentioning
confidence: 99%